Hubungan Kecepatan Terhadap Keterampilan Dribbling Pada Permainan Futsal Di Akademi Dehasen Kota Bengkulu - Echa Sandela; Meki Saputra; Feby Elra Perdima (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
Based on the observations of the activities at Dehasen Academy, that the athletic abilities of the athletes were not good enough that can cause the ball out of control. This problem is thought to be caused by several factors including the low speed of the athlete. This study aims to find out the correlation of the athlete’s speed towards Dribbling skills. The method of this study is the correlation method. The population of this study was 25 man players from Dehasen Academy Futsal club, while the samples were taken through total sampling. The place for conducting research at the Unived futsal field collected during April 2019. Speed data was taken with a 40 meter sprint test, and Dribbling skills data taken by the Dribbling test. The data analysis in this study used techniques with correlation analysis. The results of data analysis show that there is a significant correlation between speed (X) on dribbling skills in futsal athletes at Dehasen Academy of Bengkulu City, with a value of rxy = 0.95> r (0.05) (25) = 0.396